Treatment of multi-dimensional data to enhance neural network estimators in regression problems - Altun, H.; Bilgil, A.; Fidan, B. C. (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
This paper proposes and explains a data treatment technique to improve the accuracy of a neural network estimator in regression problems, where multi-dimensional input data set is highly skewed and non-normally distributed. The proposed treatment modifies the distribution characteristics of the data set. The prediction of the suspended sediment, which is an important problem in river engineering applications, will be considered as a case study. Conventional approaches lack in providing high accuracy due to the inherently employed simplicity in order to obtain empirical formulae. On the other hand, artificial neural networks are able to model the non-linear characteristics of the mechanism of the sediment transport and have a growing body of applications in diverse applications in civil engineering. It will be shown that a significant enhancement and superior score in accuracy, compared with the classical approaches, are obtainable when the proposed treatment is employed. The proposed technique is an extension to the understanding of the practical aspects of neural computing applications. Therefore the outcome of the present study is important as it is applicable to any scenario where neural network approaches are involved. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: artificial neural networks; regression; multi-layered perceptron; sediment transport; skewness; training data treatment; BED-LOAD TRANSPORT; NONUNIFORM SEDIMENT; RIVERS; MODEL; Computer Science; Engineering; Operations Research & Management Science